Leishmanial lipid affords protection against oxidative stress induced hepatic injury by regulating inflammatory mediators and confining apoptosis progress. Issue 2 (22nd January 2015) - Chatterjee, Nabanita; Das, Subhadip; Bose, Dipayan; Banerjee, Somenath; Jha, Tarun; Saha, Krishna Das
Highlights Leishmanial lipid (pLLD) improves CCl4 induced hepatic insult. pLLD reduces oxidative stress and inflammatory injury. It also down-regulates apoptotic protein during hepatic intoxication.